Hubungan Personal Hygiene dengan Riwayat Menderita Diare Pada Anak - Akbar Asfar; Sudarman Sudarman (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2019)
Abstract. Diarrhea is a condition of abnormal or unusual excretion, marked by an increase in dilution volume. There are several factors that can cause diarrhea including infection factors, malabsorption factors, food factors, psychilogical factors, environmental factors and lack of personal hygiene factors. This study aims to determine the relationship of personal hygiene with a history of suffering from diarrhea in school-age children in SDAI BAZNAS Sul-Sel Makassar City in 2018. The research design used analytic survey with Cross Sectional Study approach. The population taken in this study were 57 School Students in SDAI BAZNAS Sul-Sel, Makassar City, with total sampling techniques. Relationship testing is done by using the Chi-Square statistical test with a significance level of α <0.05. The results showed that there was a relationship between personal hygiene with a history of suffering from diarrhea in students of the Indonesian Elementary School Children (SDAI) of Makassar City BAZNAS as many as 25 (86.2%) students who had less personal hygiene with a history of diarrhea with a value of ρ = 0.006 and α <0.05. This study concluded that personal hygiene has a close relationship to the occurrence of diarrheal diseases in students so it is suggested that there is socialization and health education about personal hygiene that is good for students and societyAbstrak. Diare adalah suatu keadaan pengeluran tinja yang tidak normal atau tidak seperti biasanya, ditandai dengan peningkatan volume keenceran. Ada beberapa faktor yang dapat menyebabkan terjadinya diare diantaranya adalah faktor infeksi, faktor malabsorbsi, faktor makanan, faktor psikilogis, faktor lingkungan dan faktor personal hygiene yang kurang. Penelitian ini bertujuan untuk mengetahui hubungan personal hygiene dengan riwayat menderita diare pada anak usia sekolah di SDAI BAZNAS Sul-Sel Kota Makassar Tahun 2018. Desain penelitian yang digunakan survey analitik dengan pendekatan Cross Sectional Study. Populasi yang diambil dalam penelitian ini yaitu Siswa Sekolah di SDAI BAZNAS Sul-Sel Kota Makassar sebanyak 57 siswa dengan tehnik total sampling. Uji hubungan dilakukan dengan menggunakan uji statistik Chi-Square dengan tingkat kemaknaan α < 0,05.Hasil penelitian menunjukkan bahwa ada hubungan personal hygiene dengan riwayat menderita diare pada siswa Sekolah Dasar Anak Indonesia (SDAI) BAZNAS Sul-Sel Kota Makassar sebanyak 25 (86,2%) siswa yang memiliki personal hygiene kurang dengan riwayat menderita diare dengan nilai ρ=0,006 dan α < 0,05. Penelitian ini disimpulkan bahwa personal hygiene memiliki hubungan yang erat terhadap terjadinya penyakit diare pada siswa sehingga disarankan adanya sosialisasi serta penyuluhan kesehatan tentang personal hygiene yang baik kepada siswa dan masyarakat.